Feasibility Study on Fabricating Millimeter-wave Passive Circuits using 3D Printing Technique: Patch Antenna Case Study - Chongcheawchamnan, Mitchai (Journal of Digital Communications, 2024)
This article studies the feasibility of utilizing 3D printers to fabricate millimeter-wave passive circuits. In this research, 3D printers were studied and categorized into 3 groups of techniques; Fused Deposition Modeling/ Fused Filament Fabrication (FDM/ FFF), Stereolithography (SLA), and Selective Laser Sintering (SLS). The advantages, disadvantages, and limitations of each technique were analyzed, taking into account their technical competency, workpiece quality, and cost. Subsequently, the potential of creating millimeter-wave circuits using the aforementioned 3D printing techniques was evaluated. The case study involved fabricating a microstrip-fed patch antenna at 40 GHz using each of the three printing techniques. The dimensional variations of the microstrip line and the impact of surface roughness resulting from each 3D printing technique, which could lead to increased losses in the circuit, were also assessed. The study found that FDM/ FFF and SLA techniques were more suitable for fabricating millimeter-wave circuits compared to the SLS technique due to lower dimensional variations and smoother surface finishes, and the performance of the millimeter-wave circuits created met the design.